2014
DOI: 10.1590/s0100-06832014000600014
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the artificial neural network with parcial least squares for prediction of soil organic carbon and pH at different moisture content levels using visible and near-infrared spectroscopy

Abstract: SUMMARYVisible and near infrared (vis-NIR) spectroscopy is widely used to detect soil properties. The objective of this study is to evaluate the combined effect of moisture content (MC) and the modeling algorithm on prediction of soil organic carbon (SOC) and pH. Partial least squares (PLS) and the Artificial neural network (ANN) for modeling of SOC and pH at different MC levels were compared in terms of efficiency in prediction of regression. A total of 270 soil samples were used. Before spectral measurement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…For example, Wijewardane et al [16] used an MIR spectral library to show superior model performance using ANN compared with PLSR for all soil properties (9 out of 12) except clay, silt and sand. In contrast, PLSR models were superior compared with ANN when predicting soil pH at soil moisture levels below 20% using a vis-NIR spectral library [43]. Similarly, a comparison between PLSR and Cubist using MIR data showed that Cubist outperformed the former in the prediction of total carbon and clay, but the prediction of cation exchange capacity was better using a PLSR model [38].…”
Section: Introductionmentioning
confidence: 96%
“…For example, Wijewardane et al [16] used an MIR spectral library to show superior model performance using ANN compared with PLSR for all soil properties (9 out of 12) except clay, silt and sand. In contrast, PLSR models were superior compared with ANN when predicting soil pH at soil moisture levels below 20% using a vis-NIR spectral library [43]. Similarly, a comparison between PLSR and Cubist using MIR data showed that Cubist outperformed the former in the prediction of total carbon and clay, but the prediction of cation exchange capacity was better using a PLSR model [38].…”
Section: Introductionmentioning
confidence: 96%
“…Our analysis pipeline incorporates 4 multivariate regression models and several pre-processing techniques. We tested two calibration models already applied to pears spectra for SSC quantification: Partial Least Squares (PLS) and Multiple Linear Regression (MLR) [11,12,13,14,15,24], another model that is gaining traction in Chemometrics and that has been applied in similar contexts, Support Vector Machines (SVM) [25,26] and a simple Multi Layer Perceptron (MLP) neural network for comparison purposes [27,28,29]. The numerical analysis of the data was done using Python 3.6.…”
Section: Methodsmentioning
confidence: 99%
“…The high sensitivity of vis-NIR spectroscopy has been shown to be capable to detect trace minerals such as arsenic contamination in soil [ 24 ]. However, because of the strong moisture absorption peaks in the vicinity of the SOM features within the vis-NIR spectral range, the presence of moisture in the soil interferes the interpretation of SOM content significantly [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. It has been reported that, the two strong moisture absorption peaks that are located at about 1470 nm and 1900 nm, and the relatively weaker water absorptions features at 600 nm, 738 nm and 836 nm [ 33 , 34 , 35 ], have induced spectral distortions of the SOM absorption features particularly in the vis-NIR spectral region at about 1400 nm and 1900 nm [ 25 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that, the two strong moisture absorption peaks that are located at about 1470 nm and 1900 nm, and the relatively weaker water absorptions features at 600 nm, 738 nm and 836 nm [ 33 , 34 , 35 ], have induced spectral distortions of the SOM absorption features particularly in the vis-NIR spectral region at about 1400 nm and 1900 nm [ 25 , 36 , 37 , 38 , 39 ]. The distortion of the SOM spectral features induced significant errors in the assessment of the SOM content from the moist soil using spectroscopy methods [ 27 , 28 , 29 , 30 , 31 , 32 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation